2005
DOI: 10.1681/asn.2004070528
|View full text |Cite
|
Sign up to set email alerts
|

Renal Ischemia/Reperfusion Injury

Abstract: Renal ischemia/reperfusion injury (IRI) is an important cause of acute renal failure. Cellular and molecular responses of the kidney to IRI are complex and not fully understood. ␤1 integrins localize to the basal surface of tubular epithelium interacting with extracellular matrix components of the basal membrane, including collagen IV. Whether preservation of tubular epithelium integrity could be a therapeutic approach for IRI was assessed. The effects of HUTS-21 mAb administration, which recognizes an activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 46 publications
3
19
0
1
Order By: Relevance
“…In this study, the peritubular capillary congestion and inflammatory cellular infiltration seen in the interstitium between the tubules of IRI group were in agreement with an earlier study which confirmed the occurrence of inflammatory response as a squeal of ischemia [19] . Some authors mentioned that inflammatory infiltrate is an important contributor to kidney injury as neutrophils attach to activated endothelium and accumulate particularly in peritubular capillary network of outer medulla, as early as 30 minutes after reperfusion.…”
Section: Discusionsupporting
confidence: 93%
“…In this study, the peritubular capillary congestion and inflammatory cellular infiltration seen in the interstitium between the tubules of IRI group were in agreement with an earlier study which confirmed the occurrence of inflammatory response as a squeal of ischemia [19] . Some authors mentioned that inflammatory infiltrate is an important contributor to kidney injury as neutrophils attach to activated endothelium and accumulate particularly in peritubular capillary network of outer medulla, as early as 30 minutes after reperfusion.…”
Section: Discusionsupporting
confidence: 93%
“…The incision was closed in two layers using 4-0 silk sutures, followed by topical application of garamycin cream to reduce the risk of wound infection. Sham operation: Sham-operated animals underwent the same surgical procedure, except that the clamps were not applied (15). Preparation of bone marrow derived-mesenchymal stem cells (BM-MSCs): Rat bone marrow derived, PKH26 labeled, mesenchymal stem cells (MSCs) were purchased from Biochemistry Department, Kasr Al-Ainy Medical School.…”
Section: Methodsmentioning
confidence: 99%
“…A general phenomenon during I/R is compromised cell adhesion. [1][2][3][4] Cell adhesion is tightly controlled by proper integrity of the actin cytoskeletal network, which requires ATP. 5,6 Likewise, I/R causes cytoskeletal disruption in various tissues.…”
mentioning
confidence: 99%